ENVIRONMENTAL PHILOSOPHY AND ECOLOGICAL CULTURE - Kalimat M. Alilova (Ûg Rossii: Èkologiâ, Razvitie, 2017)
Aim. The aim of the research is to study environmental problems related to the decline of culture, the importance of philosophy in overcoming private and personal interests as well as the unilateral approach of man in his relationship to nature. The study shows how philosophy can participate in the formation of ecological culture, a new ecological consciousness in man, while ecological culture is called upon to resist technocratic stereotypes and the course of history was aimed at preventing the biosphere from becoming deserted. Discussion. On the basis of the analysis of literary sources, we used the method of socio-cultural and socio-natural approaches based on the possibility of philosophy to introduce a new life into culture, new ecological values and new ecological principles. To solve these problems, environmental philosophy develops new theories. Representatives of different cultures, ethnic groups, nations, religions must learn to coexist with each other. We consider philosophy as a means of teaching rapprochement between peoples and creating new opportunities for understanding and improving the environmental situation. Cultural development makes it possible to assess the level of a man’s knowledge of nature, himself and the world around him. Ecological culture is a way of connecting man with nature on the basis of deeper knowledge and understanding. Philosophy says that you cannot move away from nature and be lauded over it since this will destroy culture. Rational doctrines tend to put a person above other living beings so the synthesis of philosophy with culture can have a positive ecological meaning. Conclusion. The findings obtained can be recommended for practical use in schools, starting from primary school, as well as in secondary special educational institutions and universities. It is necessary to work on the motivation and values of people, develop a common and ecological culture. Only a cultured person can move from satisfying his material needs to meeting the needs of the soul thus implementing a sustainable development strategy. Therefore the links between environmental philosophy and environmental culture deserve further study.